Anti-inflammatory and Antioxidant Effects of Flavonoid-Rich Fraction of Bergamot Juice (BJe) in a Mouse Model of Intestinal Ischemia/Reperfusion Injury - Impellizzeri, Daniela; Cordaro, Marika; Campolo, Michela; Gugliandolo, Enrico; Esposito, Emanuela; Benedetto, Filippo; Cuzzocrea, Salvatore; Navarra, Michele (Frontiers in Pharmacology, 2016)
The flavonoid-rich fraction of bergamot juice (BJe) has demonstrated anti-inflammatory and antioxidant activities. The aim of work was to test the beneficial effects of BJe on the modulation of the ileum inflammation caused by intestinal ischemia/reperfusion (I/R) injury in mice. To understand the cellular mechanisms by which BJe may decrease the development of intestinal I/R injury, we have evaluated the activation of signaling transduction pathways that can be induced by reactive oxygen species (ROS) production. Superior mesenteric artery and celiac trunk were occluded for 30 min and reperfused for 1 h. The animals were sacrificed after 1 h of reperfusion, for both histological and molecular examinations of the ileum tissue. The experimental results demonstrated that BJe was able to reduce histological damage, cytokines production, adhesion molecules expression, neutrophil infiltration and oxidative stress by a mechanism involved both NF-κB and MAP kinases pathways. This study indicates that BJe could represent a new treatment against inflammatory events of intestinal I/R injury.